Chapter 2 Exploring international tourism trends in the mediterranean: convergence or big divergence (2019)
After the post-WWII emergence of mass travel, the richness of the scenery of its coastal environment, its mild climate, and its impressive cultural heritage turned the Mediterranean into a significant tourist draw. The Mediterranean basin, if considered as a single area, is by far the largest global tourism destination, attracting almost a third of the world’s international tourists (306 million out of 980 million worldwide) and generating more than a quarter of international tourism receipts (190 out of 738 billion Euro worldwide). It is forecasted that the Mediterranean region will reach 500 million of international tourist arrivals by 2030 (UNWTO 2012). (GRID-Arendal, 2013). Do the tourism economy on Mediterranean region and its sector economy shares within countries in the region: converge? The following research question is asked in this paper in an effort to analyze the main problem: whether tourism trends in recent decades push the regional tourism growth in a convergence direction and can we explain and predict the probability that a hypothetical country (saying Croatia, particularly) constitute specific profile linked to convergence? The paper is organized as follows. The next section begins by literature overview and theoretical considerations about tourism convergence in the region, and after mapping out the research strategy, we introduce the dataset. The next chapter shows descriptive analyses carried out on these international tourism flow trends, while in proceeding we carry out the convergence analyses on the whole dataset. The subsequent section presents and discusses the empirical results in Principal Component Analysis (PCA) and Cluster Analysis (CA), and the final section concludes.